Development and Satisfaction Evaluation of End-of-Life Family Support Nursing Educational Program in Neonatal Intensive Care Units - Saito, Yumiko; Wakimizu, Rie; Ozawa, Noriko; Saito, Saori (Journal of Japan Academy of Nursing Science, 2025)
Objective: This study aimed to develop a nursing education program that promotes positive attitudes toward and acquisition of knowledge and skills regarding end-of-life family support in neonatal intensive care units (NICUs), and to evaluate their satisfaction with the program.Methods: The Analysis, Design, Development, Implementation, and Evaluation model of instructional design was employed to develop the program, which comprised 1.5 hours of on-demand e-learning video viewing and 3 hours of online group training. The participants were nurses who had completed Clinical Ladder Level II or higher programs working in NICUs or Growing Care Units (GCUs), having experience in end-of-life care in NICU. After completion of the program, participants evaluated it by responding to 12 survey items related to satisfaction with the educational program. Their responses were rated on a 7-point Likert scale. In addition, their opinions were obtained through free-text responses.Results: The program included 52 NICU/GCU nurses. Between 80% and 90% of participants answered “agree” or “very much agree” on all items related to their satisfaction with the program. In their free response evaluations, they mentioned “deepening of knowledge” and “learning from other facilities and role-play.” This in turn led to “reflection and clarification of own care,” “willingness to use in practice and confidence,” and “clarification of future issues.”Conclusions: The participants appeared highly satisfied with the program, confirming that the structure and content were generally appropriate and feasible. This program made it easy for nurses across facilities to participate, and the content was satisfying, suggesting that the program’s effectiveness in nursing practice is potentially recognizable.